Elderly Acceptance of Autonomous Vehicles in Malaysia: An Extended Technology Acceptance Model with Multidimensional Trust and Perceived Risk - Ho, Jen Sim; Tan, Booi Chen; Lau, Teck Chai; Khan, Nasreen; Pang, Suk Min (JOIV : International Journal on Informatics Visualization, 2025)
The emergence of autonomous vehicle technology is propagated to address the needs of the elderly and reduce other negative externalities brought by transportation mobility. However, these benefits would not be realized without widespread acceptance. This research aimed to investigate the factors influencing the acceptance of autonomous vehicles among the elderly in Malaysia. Building on the technology acceptance model with multidimensional trust, perceived risks, and technology anxiety, a sample of 289 elderly people within Klang Valley are included in the model estimation. Results show that the mediating roles of perceived ease of use, perceived usefulness, and attitude between trust in institutions and acceptance are not supported. On the other hand, performance trust indirectly affects acceptance through perceived ease of use, usefulness, and attitude. The multidimensional perceived risks, including perceived performance risk, privacy risk, and technology anxiety, did not support the direct effect on acceptance of autonomous vehicles. These findings validate the role of multi-dimensional trusts and perceived risks in accepting autonomous cars. Trust and perceived risk in autonomous vehicles evolve; thus, a longitudinal study is recommended for future studies to understand better the elderly's acceptance of autonomous vehicles in Malaysia as the industry matures. The findings also provide important insight into industry players who design transport policies. Building trust in autonomous cars focusing on reliability and trustworthiness is vital for widespread acceptance, particularly among the elderly.